O controle interno sob a perspectiva da gestão de riscos: mito ou cerimônia institucional? - Machado, Thiago Alves (2023)
The work discusses how internal control bodies in the public sector are dealing with the application of risk-based auditing (RBA). This type of audit is the order of the day for the control area's expressive bodies, such as the Federal Audit Court (TCU) and the Office of the Comptroller General (CGU), besides being an initiative encouraged by internationally recognized audit institutions. The objective of the analysis is to seek elements in order to verify whether the implementation of ABR has been done in a ceremonial way or not. To this end, the adoption of the instrument by the Office of the Comptroller General of the State of Minas Gerais (CGE/MG) is used as an analytical reference. The main theoretical lens of the study is sociological neo-institutionalism, especially the concepts of isomorphism, myth and ceremony. The research was based on bibliographic and documental surveys, in addition to the analysis of the institutional perception of ABR in the body through the formation of focus groups, consisting of technicians and managers who work in the audit area, and interviews with the head of the State Audit Department. As a result, it was observed that there is an institutionalized ABR methodology, with a set of rules, marked notably by internal influences from CGE/MG's top management and external factors such as international norms and from agencies such as CGU and TCU. However, ABR is not an activity actually performed at CGE/MG, since its institutionalization process is recent, structured as of 2018, and that the ABRs performed are still exceptions, with a low representativeness, since audits with a compliance characteristic predominate. Finally, the research demonstrated a difficulty of assimilation of ABR by audit operators from the point of view of understanding and knowledge of this type of audit, and also indicated, by the case study, that the public administration environment is not yet favorable for performing ABRs. Thus, it can be said that despite the finding, to some extent, an ABR can be institutionalized by legitimation elements with isomorphic characteristics, but in practice the ABR points to a ceremonial adoption of the instrument by the internal control system.